Persistent DNA damage signaling and DNA polymerase theta promote broken chromosome segregation. - Clay, D.E.; Bretscher, H.S.; Jezuit, E.A.; Bush, K.B.; Fox, D.T. (Journal of Cell Biology, 2021)
Cycling cells must respond to DNA double-strand breaks (DSBs) to avoid genome instability. Missegregation of chromosomes with DSBs during mitosis results in micronuclei, aberrant structures linked to disease. How cells respond to DSBs during mitosis is incompletely understood. We previously showed that Drosophila melanogaster papillar cells lack DSB checkpoints (as observed in many cancer cells). Here, we show that papillar cells still recruit early acting repair machinery (Mre11 and RPA3) and the Fanconi anemia (FA) protein Fancd2 to DSBs. These proteins persist as foci on DSBs as cells enter mitosis. Repair foci are resolved in a stepwise manner during mitosis. DSB repair kinetics depends on both monoubiquitination of Fancd2 and the alternative end-joining protein DNA polymerase ?. Disruption of either or both of these factors causes micronuclei after DNA damage, which disrupts intestinal organogenesis. This study reveals a mechanism for how cells with inactive DSB checkpoints can respond to DNA damage that persists into mitosis.